ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN (Pada Biro Bina Sosial Kantor Gubernur Provinsi Sumatera Barat) - Reza Safitri (JIAGANIS, 2018)
AbstractThe purpose of this study was to determine the influence of leadership, motivation, and satisfaction towards the performance of employees at the bureau of community development of the social office of the governor of west sumatra in partial. Penelitian ini merupakan penelitian populasi sampel karena yang diteliti adalah seluruh karyawan biro bina sosial yang berjumlah 64 orang. Sedangkan metode pengumpulan data penelitian menggunakan metode kuesioner, wawancara dan dokumentasi. Metode analisis data dalam penelitian ini menggunakan analisis responden, deskriptif persentase, dan analisis regresi berganda.The Data collected were analyzed using t test and F test, and coefficient of determination. The conclusion is the Leadership has positive and significant influence on employee performance bureau of community development social with donations by 34.1%; work Motivation have an influence on the performance of the employees of the bureau of community development social donations amounted to 20.3%; job Satisfaction has a positive influence on the performance of the employees of the bureau of community development social with a contribution of 21.1%; Leadership, work motivation and job satisfaction have a positive influence to the value 38,710 and significant of 0.000. Sarann that the author gave that sought so that leaders can participate in the provision of responsibilities, the bureau should create an award for outstanding employees for driving motivation , as well as improving job satisfaction from the work.Keywords : Leadership, Work Motivation, Job Satisfaction, employee Performance